Knowledge, attitude and practice study on pharmacovigilance among nursing students and staff before and after a training session at a tertiary care hospital in India - Gafoor, Abdul; Mutha, Amit S.; Sahai, Jyotsna; Sankpal, Jitendra T. (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Adverse drug reactions (ADRs) contribute to significant morbidity, mortality and healthcare costs. Pharmacovigilance is essential for detecting and preventing ADRs in which nurses can play a key role. However, their involvement is very limited in this domain. The study aims to assess the knowledge, attitude and practices (KAP) among nursing students and staff regarding pharmacovigilance and the impact of a structured training session on them. Methods: A quasi-experimental, cross-sectional study was conducted at a tertiary care hospital. Nursing students and staff completed a pre-validated questionnaire before and after a training session covering pharmacovigilance concepts and ADR reporting. Pre and post session responses were compared using basic statistics. Results: Seventy participants (43 students, 27 staff) completed the study in which 54.3% reported no prior pharmacovigilance training. Post-training, the knowledge and awareness of ADR reporting procedures increased, with a positive attitude even before the session. The percentage recognizing ADR reporting as a nursing responsibility increased to 98.5%. While there were concerns of increased workload and legal consequences, 94.3% expressed interest in further training. Conclusions: Training and awareness activity effectively increased KAP on pharmacovigilance among nurses. While knowledge and attitude improved, barriers exist for ADR reporting. Integrating pharmacovigilance into nursing education and addressing systemic challenges will positively impact drug safety awareness and monitoring. This study provides empirical evidence on the impact of focused training, supporting the development of strategies to improve pharmacovigilance awareness and reporting among nursing professionals.